2007
DOI: 10.5194/acp-7-4459-2007
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical validation of temperature retrieved by the ESA processor from MIPAS/ENVISAT atmospheric limb-emission measurements

Abstract: Abstract. The Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) has been operating since March 2002 onboard of the ENVIronmental SATellite of the European Space Agency (ESA). The high resolution (0.035 cm −1 full width half maximum, unapodized) limb-emission measurements acquired by MIPAS in the first two years of operation have very good geographical and temporal coverage and have been re-processed by ESA with the most recent versions (4.61 and 4.62) of the inversion algorithms. The products o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 38 publications
3
53
0
Order By: Relevance
“…The top SSU channel covers a rather broad atmospheric region and its weighting function is centered at about 1.5 hPa, while that of AMSU-A is narrower and centered at about 2.5 hPa. Several recent, middle atmosphere temperature validation studies have indicated that the operational temperatures are too warm above 45 km and by as much as 5 to 10 K in the lower mesosphere at the low latitudes (Ridolfi et al, 2007;Gille et al, 2008;Masiello et al, 2010). It is suspected that there is also a warm bias for the SAGE II temperatures, especially after mid-2001.…”
Section: Comparisons Between Sage Haloe and The Brasseur Modelmentioning
confidence: 99%
“…The top SSU channel covers a rather broad atmospheric region and its weighting function is centered at about 1.5 hPa, while that of AMSU-A is narrower and centered at about 2.5 hPa. Several recent, middle atmosphere temperature validation studies have indicated that the operational temperatures are too warm above 45 km and by as much as 5 to 10 K in the lower mesosphere at the low latitudes (Ridolfi et al, 2007;Gille et al, 2008;Masiello et al, 2010). It is suspected that there is also a warm bias for the SAGE II temperatures, especially after mid-2001.…”
Section: Comparisons Between Sage Haloe and The Brasseur Modelmentioning
confidence: 99%
“…Besides a high performance and flexibility of the pointing system the suitability of MIPAS-B to validate instruments like ILAS-II is based mainly on its high spectral resolution (about 0.07 cm −1 after apodization) allowing the separation of individual spectral lines from continuum-like emissions in combination with a high radiometric accuracy. A comprehensive overview and description of the instrument is given by Friedl-Vallon et al (2004) Cortesi et al, 2007;Höpfner et al, 2007;Ridolfi et al, 2007;Wang et al, 2007;Wetzel et al, 2007). The flight duration of more than 15 h from 18:22 UTC (20 March) to 09:38 UTC (21 March) also permitted a good match of the sunrise measurement of the ILAS-II sensor aboard ADEOS-II.…”
Section: Instruments and Data Analysismentioning
confidence: 99%
“…The bias and the standard deviation of these discrepancies are consistent with those obtained when comparing MIPAS data to correlative measurements; however, the detected bias to ECMWF data has a peculiar altitude dependence. But this seems to be a problem of the ECMWF temperature distribution (see Ridolfi et al, 2007).…”
Section: The Esa Workhops On Validation In May 2004 and December 200mentioning
confidence: 99%